Effect of Desensitizing Products on the Morphology of Dentin Substrate - Rafael de Lima Pedro; Gabriel Maia Krammer; Luise Gomes da Motta; Marcelo de Castro Costa (Journal of Dental Problems and Solutions - Peertechz Publications, 2016)
The aim of this study was to determine the action of desensitizing materials on bovine dentin. Four extracted healthy bovine molars were selected out of which 5 blocks from cervical region of each tooth were obtained, resulting in a 5x5mm final area. To compose the negative control group (group B), the samples were separated and not submitted to any treatment. For the positive control (Group A) the blocks were treated with 37% phosphoric acid. For allow to use the same dentin samples for all groups ( 2 controls and 3 test group), the experiment group contained twelve dentin surface blocks divided in 5 groups (n=4 in each group), as manufacturers' recommendations, there were used: Dessensibilize KF 2% - 5% Potassium nitrate and 2% sodium fluoride (C); Fluoride Gel - 2% sodium fluoride (D), Colgate Sensitive Pró-Alívio® Arginine 8% (E) and Calcium carbonate-based toothpaste (F). The samples were analyzed in Scanning Electron Microscopy (SEM) and used the ANOVA and Tukey tests (p<005). The number and diameters of dentinal tubules were compared across the various groups. The samples from group E had a higher quantity of deposits on the peritubular and intertubular dentin with most closed tubules. Although, the groups A and B presented more opened dentinal tubules. However, only A has deposited a substratum from the reaction with desensitizing materials on the peritubular and intertubular dentin indicating same closed tubules. The analysis of the diameters of the tubules showed significant differences in groups B and C when compared to the other groups.